1977
DOI: 10.1007/bf00268670
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and turnover of ribosomal proteins in the absence of 60S subunit assembly in Saccharomyces cerevisiae

Abstract: We have measured the synthesis and stability of ribosomal proteins in a temperature sensitive strain of yeast which at the restrictive temperature is specifically blocked in the processing of 27S ribosomal precursor RNA. We find that in the absence of 60S ribosomal subunit assembly, the synthesis of all the ribosomal proteins studied continued. However, the proteins of the 60S subunit fail to accumulate and are rapidly degraded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
1

Year Published

1980
1980
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 21 publications
0
51
0
1
Order By: Relevance
“…In a 3-min pulse, the unassembled half-life of these proteins would have to be less than 1 min if turnover alone were responsible for the observed labeling. The half-life of 60S ribosomal proteins synthesized in the absence of rRNA was measured previously at 7 to 20 min (11). In that experiment proteins L2, L5, and L13 (designated rp2, rp8, and rpl5 in reference 11) had half-lives of 24, 8, and 13 min, respectively.…”
Section: Methodsmentioning
confidence: 96%
“…In a 3-min pulse, the unassembled half-life of these proteins would have to be less than 1 min if turnover alone were responsible for the observed labeling. The half-life of 60S ribosomal proteins synthesized in the absence of rRNA was measured previously at 7 to 20 min (11). In that experiment proteins L2, L5, and L13 (designated rp2, rp8, and rpl5 in reference 11) had half-lives of 24, 8, and 13 min, respectively.…”
Section: Methodsmentioning
confidence: 96%
“…Previously it was shown that the temperature-sensitive mutant rrp1-1 is defective in the processing of 27S pre-rRNA to produce 25S rRNA and deficient in 32 P -labeled 60S ribosomal subunits (Andrew et al 1976;Gorenstein and Warner 1977;Fabian and Hopper 1987). We sought to examine the function of Rrp1p in more detail by constructing and assaying a mutant strain containing a conditional null allele of RRP1, and by assaying pre-rRNA processing at higher resolution in rrp1 mutants.…”
Section: Depletion or Inactivation Of Rrp1p Leads To Defects In Biogementioning
confidence: 99%
“…Although it was shown that processing of 27S pre-rRNA to mature 25S and 5.8S rRNAs was blocked in the rrp1-1 mutant, tools were not yet available to identify and distinguish the 27SA 2 , 27SA 3 , 27SB S , 27SB L , and 25.5S pre-rRNA processing intermediates (Andrew et al 1976;Gorenstein and Warner 1977;Fabian and Hopper 1987). Thus, the exact nature of the 27S pre-rRNA processing defect in the rrp1-1 mutant was not clear.…”
Section: Rrp1p Is Important For Two Steps In Pre-rrna Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…The coordination did not, however, appear to be at the level of synthesis. Indeed, in most cases, inhibited synthesis of one component did not effect the synthesis of the other [12,13,16]. The reduced accumulation of the latter was due to increased degradation.…”
Section: Discussionmentioning
confidence: 95%